Software development on thermoelectrics applications - Maung Thein Soe. (2008)
The main objective of this project is to develop a platform-independent and interactive software application, which is capable of selecting thermoelectric module(s) available from different manufacturers. And also to provide steps required for an optimum design of a complete Thermoelectric Cooling System by exploring the important thermoelectric concepts and the recent advancements.